Catalytic activity vs. size correlation in platinum catalysts of PEM fuel cells prepared on carbon black by different methods - Nores Pondal, Federico Jose; Vilella, Irene María Julieta; Troiani, Horacio Esteban; Granada, Mara; de Miguel, Sergio Ruben; Scelza, Osvaldo Antonio; Corti, Horacio Roberto (Pergamon-Elsevier Science Ltd, 2009)
Fil: Nores Pondal, Federico Jose. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes; Argentina